1989
DOI: 10.1017/s0954579400000213
|View full text |Cite
|
Sign up to set email alerts
|

Stability of behavior problems in very young children

Abstract: This study examined the stability of behavior problems in 44 low SES children ages 2–5 years using the preschool and standard versions of Achenbach's Child Behavior Checklist. While scores for the present sample did not differ significantly from Achenbach's standardization sample at age 2, scores at ages 4 and 5 were somewhat elevated; this was true for the Total score, as well as for the two broad-band scores (Internalizing and Externalizing). At all ages, the Internalizing and Externalizing scores correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
106
2
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(118 citation statements)
references
References 35 publications
(37 reference statements)
8
106
2
2
Order By: Relevance
“…This trend has also been observed in previous studies (see Edwards et al, 2009). Emotional difficulties in three-year-olds were reported to be highly stable across 12 months, .75 and .74 based on maternal and paternal reports respectively (Edwards et al, 2009), and stable only between ages 4 and 5 (Rose et al, 1989), whereas in a study by Redmond and Rice, a downward trend in emotional difficulties was found for the period of 6-8 years (2002).…”
Section: Changes In Social Behaviour During the Early Yearssupporting
confidence: 84%
See 1 more Smart Citation
“…This trend has also been observed in previous studies (see Edwards et al, 2009). Emotional difficulties in three-year-olds were reported to be highly stable across 12 months, .75 and .74 based on maternal and paternal reports respectively (Edwards et al, 2009), and stable only between ages 4 and 5 (Rose et al, 1989), whereas in a study by Redmond and Rice, a downward trend in emotional difficulties was found for the period of 6-8 years (2002).…”
Section: Changes In Social Behaviour During the Early Yearssupporting
confidence: 84%
“…A peak of socially inappropriate behaviour, aggression in particular, has been observed in three year olds (Egger and Angold, 2006), followed by a decline in oppositional difficulties between the ages of 3 and 5 years (Lavigne et al, 1996). In contrast, eEmotional difficulties in three-year-olds were reported to be highly stable across 12 months, with coefficients of .75 and .74 based on maternal and paternal reports respectively (Edwards et al, 2009), and stable only between ages 4 and 5 (Rose et al, 1989), whereas in a study by Redmond and Rice, a downward trend in emotional difficulties was found for the period of 6-8 years (2002).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has documented that internalizing symptoms in childhood predict depression during adolescence (Rose, Rose, and Feldman, 1989). Externalizing behaviors (i.e., aggression, delinquency) predict later problem behaviors including drug use and antisocial behavior (Brook, Whiteman, Finch, and Cohen, 1996), as well as psychiatric disorders (Brook, Richter, and Rubenstone, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Consequently, it is important to examine the etiology and prevention of negativity and its sequelae in young children.…”
mentioning
confidence: 99%